Evaluation of The Effect of Smoking and Chronic obstructive pulmonary disease(COPD) on Lipid profile - Mahdi Mahmoud , Ali; Fawzi Jameel , Basil; Waheeb AL – Obaidy , Muhammed; Nema Abd , Mustafa (Diyala Journal of Medicine, 2022)
Background: (COPD) disease is consider an important disease that threat our life in recent years and its result mostly from smoking .the patients who affected by this disease will be at higher risk of death caused by frequent exacerbation ,also chronic obstructive pulmonary disease may influence the lipid profile regardless of smoking status. Objective: To assessment the effect of COPD and smoking on lipid profile. Patients and Methods: This case control study included 50 patients suffer from (COPD) and other age- and sex-matched 50 smokers (≥ 20 pack/yeas) healthy people. Demographic and clinical data were collected through a direct interview with each participant. Fasting lipid profile was measured according to the standard protocols. Results: Mean serum level of TG and vLDL in smokers with COPD was 192.4±46.91 mg/dl and 61.8±12.23 mg/dl, respectively compared with 135.5±23.8 mg/dl and 32.68±14.8 mg/dl, respectively in smokers without COPD, with significant differences. Furthermore, the frequency of abnormal triglyceride value among smokers with COPD was 36% compared to 12% among smokers who don’t have this disease . (OR= 4.12. 95%CI= 1.47-11.55, p= 0.007). Similarly, the frequency of abnormal vLDL among smokers with COPD was 18% compared to 4.12% among smokers without COPD (OR= 5.27. 95%CI= 1.08-25.8, p= 0.040). In smokers with COPD, smoking displayed a positive significant correlation with TG (r= 0.325, p= 0.021) and vLDL (r= 0.333, p= 0.018). In smokers without COPD, smoking had a positive and marked association with TC (r= 0.377, p= 0.007) Conclusion: COPD is associated with negative effects on the lipid profile. In particular, triglycerides and very low-density lipoprotein cholesterol are mostly affected. Aside from COPD, smoking can also be associated with elevated lipids/lipoproteins that exceed normal limits at times.